Madagascar: Agricultural R&D Indicators Factsheet - Magne Domgho, Léa Vicky; Randriamanamisa, Rivonjaka; Stads, Gert-Jan (International Food Policy Research Institute, 2017)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also features a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.